7P's marketing strategy affecting customer's purchase intentions towards Global Market Operation of Deutsche Bank, Kuala Lumpur / Mohd Khairi Mohd Hanafiah - Mohd Hanafiah, Mohd Khairi (Faculty of Business and Management, 2008)
The purpose of this study was to assist Global Market Operation of Deutsche Bank Malaysia Berhad, Kuala Lumpur (GM OPS) in determining their services marketing mix. It is to identify the current strategies that have been practiced by Global Market Operation of Deutsche Bank in term of the 7P's. The research is also focusing on the perception of the customers towards the strategy that have been practiced by Global Market Operation of Deutsche Bank and also to induce the customer's suggestions and ideas on how Deutsche Bank can improve their performance to attract new customers and retain old customers. The result indicates that the staffs / personnel factor explained the highest proportion of customer's purchase intentions towards GM OPS of Deutsche Bank Malaysia Berhad. The weakest link in the 7P's marketing strategy would be the promotional activities and process of banking transaction that are not aggressively and accurately performed in order to create customer awareness and enhance customer's satisfactions. The researcher used descriptive research in order to conduct the research on the issues. 60 questionnaires were distributed to customers of Global Market Operation of Deutsche Bank and these respondents were selected using non probability sampling technique. Questionnaires were distributed as the survey instrument as the source of primary data. The researcher also conducts several sessions of interviews with the management of GM OPS of Deutsche Bank to gain the information relevant to achieve the objectives of the study.